2014
DOI: 10.1371/journal.pone.0085406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ensiled Mulberry Leaves and Sun-Dried Mulberry Fruit Pomace on Finishing Steer Growth Performance, Blood Biochemical Parameters, and Carcass Characteristics

Abstract: Fifty-one Simmental crossbred steers (357.0±16.5 kg) were used to compare a standard total mix ration (TMR) with variants on animal performance, ruminal fermentation, blood biochemical parameters, and carcass characteristics. Corn grain and cotton seed meal were partially replaced by ensiled mulberry leaves (EML) or sun-dried mulberry fruit pomace (SMFP). Experimental diets had similar amounts of crude protein (CP), acid detergent fiber (ADF), and metabolizable energy (ME). Animals were divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…It is possible that effects of this Figure 2. Similarly, other studies found no improvements in carcass characteristics, noncarcass components, or wholesale yield by addition of whole plants or plant extracts with antioxidant properties to feedlot diets of sheep (Tavasoli et al, 2009;Omer et al, 2013), male goats (Karami et al, 2010), or steers (Zhou et al, 2014). No significant FA × days on feed interaction or FA main effect (P ≥ 0.20) were observed for blood serum total protein and urea.…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that effects of this Figure 2. Similarly, other studies found no improvements in carcass characteristics, noncarcass components, or wholesale yield by addition of whole plants or plant extracts with antioxidant properties to feedlot diets of sheep (Tavasoli et al, 2009;Omer et al, 2013), male goats (Karami et al, 2010), or steers (Zhou et al, 2014). No significant FA × days on feed interaction or FA main effect (P ≥ 0.20) were observed for blood serum total protein and urea.…”
Section: Discussionmentioning
confidence: 87%
“…() (25·9%) and higher than those published by Zhou et al . () (14·1%). Ether extract content (3·5 and 2·1% in leaves and TST respectively) was higher than the value reported by Hurtado et al .…”
Section: Discussionmentioning
confidence: 99%
“…agroforestry or agrosilvopastoral systems). Traditionally developed in the silkworm production industry (Katsumata, ; Tikader and Kamble, ; Zhou et al ., ), the nutritional quality of mulberry forage has been substantially improved for these purposes over time, resulting in high digestibility forage with higher crude protein and energy, and lower cell wall contents. Its nutritional traits have led to its use in unconventional feeding systems for ruminants (Benavides, ) and for non‐ruminant species such as swine (Contino et al ., ; Ly and Samkol, ), poultry (Machii, ; Riyadh et al ., ) or rabbits (Deshmukh et al ., ; López et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…The biomass yield of fresh mulberry leaves is approximately 25–30 tons/ha/year. Extracts or constituents of mulberry leaves have been reported to possess anti‐inflammatory, antioxidant (Zhang et al, ), antiobesity, antidiabetic, hypolipidemic and neuroprotective properties (Chen et al, ; Zhou, Zhou, Ren, & Meng, ). Mulberry leaves are succulent and characterized by high crude protein (CP; 19.4%) and low neutral detergent fibre (NDF; 36.1%) (Sahoo, Singh, & Sharma, ), meaning they represent a potential feed source for herbivores and monogastric animals.…”
Section: Introductionmentioning
confidence: 99%